Halal beef handling in Nigeria : the abattoir workers’ perspective / Carrie Amani Annabi and Jinadu Lolade Ahmed - Annabi, Carrie Amani; Ahmed, Jinadu Lolade (Faculty of Business and Management, 2015)
Despite Nigeria‟s large Muslim population of 77.3 million citizens, very little research has been carried out in terms of addressing Halal needs in Nigeria. This study reviewed the perspective of abattoir workers‟ involved with Halal beef in two abattoirs in Abuja. The research made use of primary data gathered by conducting telephone interviews, using semi-structured interview questions. Although the National Agency for Food and Drugs Administration Control (NAFDAC) guidelines which govern Halal beef handling in Nigeria proved to have commonalities with those recommended by the Jurisdiction of Department of Islamic Development in Malaysia, (JAKIM), the findings revealed that there was a general lack of awareness about either of those guidelines amongst the abattoir workers interviewed. The abattoir workers that participated indicated that their perception of what constitutes Halal beef handling best practice was based on personal opinion. Thus, there is the need to create better awareness on the current guidelines for Halal beef handling provided by NAFDAC. Furthermore there is a need for Halal beef handling training for the abattoir workers in Nigeria. This was evidenced in the fact that additional Halal beef logistics activities such as packaging, storage and transportation were found to be carried out by third party logistics (3PLs) organizations which made it difficult to ascertain the Halal integrity of the Halal beef supply chain.